(untitled) (Journal of Humanities and Social Sciences Research, 2022)
The game of basketball requires comprehensive preparation in all aspects of physical and skill, as well as tactical, psychological and educational. This is achieved by preparing comprehensive training curricula for the development of players, including young people, being the basis for achieving the best results and reaching a high level. Through the experience of the two researchers and their knowledge of some research and training curricula, he saw that these curricula and research did not dedicate a large amount of their contents to modern training methods, as well as the lack of interest in them, which negatively affected the performance of young players, the complex defensive skills, and a clear addition when performing them, and therefore because this skill always leads to difficult circumstances. With a striker nearby, which negatively affects the results of the match and the research objective is to prepare dynamic lactate exercises in developing the complex defensive skills of young basketball players. Identifying the effect of dynamic lactate workouts in building complicated defensive skills, a good impact on the development of young basketball players’ complex defensive skills. The researchers used the experimental method as a research procedure that fits the research objectives The research community consisted of Al-Hilla basketball players aged (16-18) years, who numbered 12 players, where the community was divided randomly into two groups (experimental and control), where the number of each group reached (6) players. Among the most important conclusions of the research is that there is a development of Compound defensive skills for young basketball players for the experimental group and the control group, and one of the most important recommendations is to pay attention to developing physical abilities in a way that precedes and accompanies the development of offensive skills for young basketball players.